Interpretations of Chinese Aesthetic Modernity: A Case Study of the Multifaceted Construction of the Wukong Image - Wu, Tianqi; Cui, Jing; Ma, Tianyi (International Journal of Humanities and Social Science, 2026)
Due to the long-standing and continuously inherited nature of Chinese culture, its philosophical thought inherently possesses the quality of drawing upon the wisdom of ancient sages. The aesthetic modernity within Chinese philosophy distinguishes itself from the Western model of modernity, which centers on temporal progress. Instead, it is rooted in the spatial continuity and cultural persistence, generating its own evolution and transformation within the tension between tradition and modernity. Chinese philosophy of information introduces the concept of symbolic information. Chinese aesthetic modernity primarily manifests itself through the reinterpretation and re-cognition of corresponding symbolic information. The classical Chinese mythological figure, Sun Wukong, is undoubtedly a highly representative cultural symbol of this kind. The spirit, personality, metaphors, and other abstract connotations embodied by Wukong constitute symbolic information; this symbolic information is the core and essence of Wukong. This symbolic information has undergone significant changes across different historical periods, exhibiting a deep evolutionary characteristic shaped by changing times and aesthetic interactions. Wukong stands as a typical example of a figure subjected to multi-dimensional reinterpretation and re-creation within modernity. By activating and reinterpreting traditional symbolic information within a global context, it reconstructs a new and robust cultural subjectivity. Furthermore, this continuous process of cultural adaptation highlights the dynamic resilience of Chinese aesthetic paradigms when confronted with contemporary globalized narratives. Ultimately, the multifaceted construction of the Wukong image serves as a profound theoretical lens through which scholars can better understand the broader mechanisms of cultural modernization and symbolic evolution.